Positron-helium scattering at medium energies - Adhikari, S. K.; Ghosh, A. S. (Elsevier B.V., 1996)
We present results for medium-energy elastic, inelastic [transition to He(1s2(1)s), He(1s2(1)p), He(1s3(1)s), and He(1s3(1)p) states], capture [to Ps(1s), Ps(2s), and Ps(2p) states of the positronium (Ps) atom] and total cross sections of positron-helium scattering in the close coupling approach using realistic wave functions.